The governance core 2.0 school boards, superintendents, and schools working together - Campbell, Davis; Fullan, Michael; Kavanaugh, Babs (Corwin, 2025)
"A common vision driven by a shared moral imperative. That is what this book is about. Our vision is of a governance system, school board and superintendent, working together as a cohesive, unified team with a common vision driven by a shared moral imperative. This is a dynamic, powerful role for school boards. It assumes that governance is a basic function of the organization, an integral part of the system, setting the direction of the district, assuring the achievement of strategic goals and the moral imperative, holding the district accountable and providing leadership to the community. Most importantly it is a governance system that fulfills its responsibility to all the children and the community it serves"--